Pengaruh Praktik Kerja Lapangan dan Soft skill Terhadap Kesiapan Kerja Siswa Konsentrasi Keahlian Kuliner di SMK Negeri Kota Malang - Agung Fachri Julianto; Nunung Nurjanah; Lismi Animatul Chisbiyah; Laili Hidayati (Universitas Cokroaminoto Palopo, 2025)
The high unemployment rate among vocational high school (SMK) graduates in Indonesia, particularly in Malang City, signals a pressing need to strengthen students’ work readiness. Despite technical competencies acquired at school, many graduates struggle to meet industry expectations due to gaps in non-technical skills. This study aims to examine the influence of field work practices (PKL) and soft skills namely written communication, problem solving, leadership, and teamwork on the work readiness of culinary students at three public vocational schools in Malang. A quantitative approach was used, involving a total population of 80 students from SMKN 3, SMKN 7, and SMKN 12 Malang, all of whom had completed their PKL. As the population was under 100, total sampling was applied. Data were collected using a validated and reliable Likert-scale questionnaire and analyzed through descriptive statistics and multiple linear regression. Prior to regression, classical assumption tests were conducted to ensure normality, linearity, and absence of multicollinearity. The results show that field work practice did not have a significant partial effect on work readiness (sig. = 0.912), nor did the soft skill aspects of written communication (sig. = 0.897) and leadership (sig. = 0.088). However, problem solving (sig. = 0.002) and teamwork (sig. = 0.000) skills significantly influenced students’ work readiness. Simultaneously, PKL and all soft skills collectively had a significant influence, accounting for 61.5% of the variance in work readiness. These findings highlight the importance of integrating targeted soft skills development especially teamwork and problem-solving into vocational education to better align with industry demands